Studi Praktek Diskriminasi Agama Minoritas di Desa Terpencil - Hidayat, Rahmad; Sauki, Muhammad (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2022)
This article discusses the dynamics of the practice of discriminating religious minorities in Oi Bura Village, Tambora District, Bima Regency, West Nusa Tenggara Province by dominant ethnic and/or religious adherents there. The practice of religious discrimination took the form of prejudice, different treatment, and political-economic restrictions experienced by Hindus as immigrants from Bali. The study case approach used in this study examined the relevance of two main aspects. These aspects include (1) the history of Oi Bura Village and the phenomenon of social segregation, and (2) the practice of discrimination against religious minorities in that village and the strategy of eliminating it through the iterative construction of social inclusion discourse. The process of separating the location of settlements between a group of people from Bali and other groups in Oi Bura Village reflects the continuity of the colonial heritage in the form of ethnic and religious residential segregation. As a result, this practice has triggered the emergence of social distances between community groups that have violated the principles of inclusion or social solidarity.